Laser polishing of additively manufactured metal parts: a review - Manco, Emanuele; Cozzolino, Ersilia; Astarita, Antonello (Surface engineering, 2022)
This paper provides a reliable state of the art of laser polishing process (LP), used to reduce surface roughness and to improve surface properties of additively manufactured metal parts. The motivation of this review and the introduction to the research topic are discussed in detail in the first part of the paper, then the fundamentals and the working principles of LP are exposed. A quantitative literature survey is also included, the main research streams are discussed, the most used laser sources and the most investigated materials are highlighted. The manuscript core is divided into five subchapters depending on the material to be polished: aluminium alloys, titanium alloys, steels, CoCr alloys and nickel alloys. Each of these discusses the laser adopted, the results obtained, the role of the process parameters and the physical phenomena ruling the process. The final section includes applications, advantages, direction of future work and main conclusions drawn.